2021
DOI: 10.1128/jb.00439-20
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphatidyl- myo -Inositol Dimannoside Acyltransferase PatA Is Essential for Mycobacterium tuberculosis Growth In Vitro and In Vivo

Abstract: Mycobacterium tuberculosis comprises an unusual cell envelope dominated by unique lipids and glycans that provides a permeability barrier against hydrophilic drugs and is central for its survival and virulence. Phosphatidyl-myo-inositol mannosides (PIMs) are glycolipids considered not only key structural components of the cell envelope but also the precursors of lipomannan (LM) and lipoarabinomannan (LAM), important lipoglycans implicated in host-pathogen interactions. Here, we focus on PatA, a membrane associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Although it plays a certain role in reducing the mortality of TB, its low targeting of macrophages leads to a low killing rate, resulting in a longer treatment cycle for patients as well as some inevitable toxic and side effects [ 4 , 5 ]. Therefore, more efficient and active killing of MTB in macrophages and reducing the emergence of drug-resistant MTB are the most pressing challenges facing TB treatment [ 6 ]. This study will also contribute to the treatment of TB, hoping to provide some reference for the effective treatment of TB patients from the breakthrough point of the nanotargeted drug delivery system.…”
Section: Introductionmentioning
confidence: 99%
“…Although it plays a certain role in reducing the mortality of TB, its low targeting of macrophages leads to a low killing rate, resulting in a longer treatment cycle for patients as well as some inevitable toxic and side effects [ 4 , 5 ]. Therefore, more efficient and active killing of MTB in macrophages and reducing the emergence of drug-resistant MTB are the most pressing challenges facing TB treatment [ 6 ]. This study will also contribute to the treatment of TB, hoping to provide some reference for the effective treatment of TB patients from the breakthrough point of the nanotargeted drug delivery system.…”
Section: Introductionmentioning
confidence: 99%
“…7 Phosphatidylinositol mannoside acyltransferase A (PatA) can add an acyl group to the 6-position of the mannose ring attached at the 2-position of the myo-inositol of PIM 2 to produce Ac 1 PIM 2 . 8 An unknown acyltransferase can add another acyl group at the 3-position of the inositol group of Ac 1 PIM 2 to synthesize Ac 2 PIM 2 . 9 In one of the strains of Mycobacterium tuberculosis , PimC had been identified that can add another mannose to the Ac 1 PIM 2 to produce Ac 1 PIM 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, they regulate the selective transport of molecules across the bacterial membranes and, as enzymes, they catalyze a myriad of biochemical reactions. The bacterial membrane constituents are represented by a substantial number of species, the amount and distribution of which also varies in space and time (6)(7)(8)(9)(10)(11)(12). Therefore, the structural diversity of membranes provides identity to bacterial cells, which strongly influence the development and maintenance of a large number of bacteria life forms.…”
Section: Introductionmentioning
confidence: 99%
“…1B ) ( 20 , 23 ). PatA was found important for the optimal growth of M. smegmatis mc 2 155 and an essential enzyme for the growth of M. tuberculosis in vitro and in vivo ( 11 , 23 ). Two models were originally proposed for the biosynthesis of Ac 1 PIM 2 in mycobacteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation